Conductivity and ion-pair formation in acetone solution as a function of pressure and temperature. - Adams, W. A. (University of Ottawa (Canada), 1967)
The equivalent conductivities of tetramethylammonium iodide, tetraethylammonium iodide, and tetra-n-propylammonium iodide in acetone solution were determined at temperatures of 25° to 55°C, and at pressures from atmospheric to 1.1 kbar. The results have been analysed by the Shedlovsky method. The limiting equivalent conductivities have been interpreted in terms of activated complex theory; the energies of activation for conductivity at constant pressure and at constant volume, and the volumes of activation for conductivity, were calculated, The hole free-volume theory of liquids has been discussed for different solvent systems and found to give a satisfactory explanation for the observed pressure and temperature coefficients of conductivity, viscosity, and self-diffusion in several solvents. The magnitude of the limiting ionic equivalent conductivity has been shown to depend in a critical way on the ionic radius and on the relative strengths of the ion-solvent and the solvent-solvent interactions. The ion-pair dissociation constants determined from the Shedlovsky analysis were used to calculate the enthalpy, the internal energy at constant volume, the entropy, the volume, and the Gibbs free energy of dissociation. The sign and magnitude of these parameters over the range of conditions of temperature and pressure investigated indicated that the free ions in acetone solution are extensively solvated and that, depending on the conditions, solvent-shared or solvent-separated ion pairs are formed. The compressibility of acetone has been redetermined at temperatures of 25° to 55°C, and at pressures from atmospheric to 1.1 kbar. The results have been fitted to the Tait equation, and values of (deltaP/deltaT) V and of the internal pressure have been calculated. The heat capacity at constant volume has also been deduced as a function of pressure and temperature. The variation of these a-rid other derived quantities has been shown to lead to conclusions about structural changes in the liquid.
Keywords: Chemistry, Physical.